The impact of credit ratings on the decision-making process behind capital structures - Gomes, Joana de Oliveira (2020)
The role of credit ratings in influencing capital structure decisions has generated a lot of discussion. This thesis intends to examine whether credit ratings directly impact the marginal financing behaviors of U.S. firms. Kisgen (2006) engaged in an earlier seminal discussion of this topic. His arguments on the discrete costs associated with credit rating levels suggest that firms near a credit rating change issue less debt relative to equity than firms farther away from a rating change. This concept became henceforth known as the Credit Rating-Capital Structure (CR-CS) hypothesis. Through the empirical analysis of 14,037 firm-years between 2001 and 2017, our work confirms Kisgen’s (2006) findings that firms with a plus or minus rating have a propensity to use less debt relative to equity, than firms in the middle, supporting the CR-CS hypothesis. However, this significance seems to be mainly driven by the minus designation. Therefore, firms with an upgrade potential do not appear to significantly adjust their debt issuing patterns. Moreover, we confirm that firms are typically most concerned about broad rating levels, in which the access to the commercial paper is affected. Lastly, we find that credit ratings have a significant effect on capital structures, both during and prior to the financial crisis periods. Overall, we provide evidence that the potential costs of downgrades directly impact capital structure decisions, and managers are thus likely to be concerned with ratings-triggered costs.